Mental Healthcare workers' experiences in managing psychiatric patients' aggression in Maseru - Libuseng M. Rathobei; Sipho W. Mkhize (AOSIS, 2023)
Background: Aggression and violence in psychiatric clinical facilities are a common case, and mental healthcare workers utilise various management strategies to combat it. It is therefore crucial for mental healthcare workers to acquire skills for the management strategies of aggressive behaviour of psychiatric patients. Aim: The aim of the study was to describe mental healthcare workers' experiences in the management strategies of aggressive and violent behaviour by psychiatric patients in Maseru district. Setting: A psychiatric hospital situated to the south in Maseru in the rural countryside and general hospital located in the western lowlands of Lesotho in the village of Morija were used. Methods: This study adopted a qualitative, exploratory, descriptive and contextual research design. There were two focus group interviews conducted per clinical facility, which consisted of six members in each group. There were four participants for individual interviews from psychiatric clinical facility and three individual interviews from general clinical facility. Results: Thematic analysis of the data resulted in themes and sub-themes. These were psychological intervention strategy, physical strategy, chemical strategy, empowerment strategy and policy strategy. Participants viewed various management strategies of aggressive and violent behaviour of psychiatric patients they utilise in clinical facilities as effective. Conclusion: The mental healthcare workers' experiences in managing aggression and violent behaviour of psychiatric patients were expression of psychological, physical, chemical, empowerment and policy strategies. Contribution: The study will enhance the knowledge, skills and attitudes regarding management strategies that mental healthcare workers can utilise in managing aggressive and violent behaviour of psychiatric patients.